Ovarian carcinoma presenting as cutaneous nasal metastasis - Ana Marta António; João Vitor Alves; João Goulão; Elvira Bártolo (Sociedade Brasileira de Dermatologia, 2016)
Abstract Metastatic ovarian cancer uncommonly presents with skin metastasis. When present, skin metastases of ovarian cancer are usually localized in the vicinity of the primary tumor. We report a case of a 58-year-old woman with a rapid growing erythematous, well-defined nodule localized on the left nasal ala. A skin biopsy was performed and histopathological and immunohistochemical findings were compatible with a cutaneous metastasis of adenocarcinoma. A systematic investigation revealed a bilateral ovarian cystadenocarcinoma associated with visceral dissemination, likely associated with nose cutaneous metastasis. We report a very uncommon case because of the presentation of ovarian carcinoma as cutaneous metastasis. To our knowledge, this atypical localization on the nose has not been described yet in the literature.